Customers’ Perception On Problems Towards Adopting Marketing Strategies Of Select Online Retailers (Journal of Namibian Studies : History Politics Culture, 2023)
E-commerce can be stated as the buying and selling of goods or services through electronic means. Like the internet, mobiles, telephones, ATMs, fax machines, etc. Online marketing talks about the techniques and strategies that are used for marketing products and services on different digital platforms. Online marketing aids in attracting customers as increasingly more people are engaged in the digital world.  The online market sector has gone through many industrial and rigid changes, which play a role in creating a shift in consumer buying attitudes. The present study makes an effort to locate the differences in the problems associated with adopting online e-retailers' marketing techniques and strategies. The study was on only 450 customers of selected online e-retailers in Cuddalore District. The study was based on primary data collected through an interview schedule. SPSS has been used to analyze the t-test and chi-square analysis has been used. The result of the study showed that problems relating to e-retailers' services are at variance among the customers of select online-retailers.